Adaptation of Tourism Actors to the Sendang Lele Tourism Object in Gentan Village Post Covid-19: Adaptasi Pelaku Pariwisata Objek Wisata Sendang Lele Desa Gentan Pasca Covid-19 - Ilham Cahyo Widodo; Anissa Fajar Lutfiah; Rendra Rizky Yulianto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Sendang Lele Gentan is one of the tourist attractions that has its own charm in the form of folklore. The story has developed in the lives of the community from generation to generation. This study aims to examine the adaptation carried out by tourism actors in the Sendang Lele tourist attraction after Covid-19. This study was conducted using a qualitative descriptive method with a purposive sampling technique. Data collection was carried out through interviews, non-participant observation, and literature studies. The results of the study showed that the Covid-19 pandemic resulted in a decrease in the number of visitors, requiring tourism actors, especially traders and POKDARWIS, to adapt. Many traders chose to sell at home, sell around, and some even closed their businesses. Through this study, it is hoped that it can provide knowledge to the wider community about the adaptation of tourism actors in the Sendang Lele Gentan tourist attraction after Covid-19.